PUTUSAN MAHKAMAH KONSTITUSI NOMOR 140/PUU-VII/2009 DAN JAMINAN KONSTITUSIONAL ISLAM NUSANTARA - Eddyono, Luthfi Widagdo (Universitas Islam Negeri Raden Intan Lampung, 2015)
The Constitutional Court Decision Number 140/PUU-VII/2009 regarding the case of judicial review of Law No. 1/PNPS/1965 about the Prevention of Abuse and/or blasphemy is very important for the study of the development of religious life in Indonesia, especially for the study of “Islam Nusantara”. This paper will describe ebates in the trial to assessed the extent to which the views of the majority of the people related with the norms of the Law. In addition, this paper also will be describe the Constitutional Court’s decision on the petition. After that, the authors examine the relationship between the Constitutional Court decision and the existence of “Islam Nusantara” in Indonesia. In conclusion, the Constitutional Court through Decision No. 140/ PUU-VII/2009 provided constitutional guarantees on religious practices like “Islam Nusantara”.